Deformation behavior of as-cast and as-extruded Mg97Zn1Y2 alloys during compression, as tracked by in situ neutron diffraction. (December 2018) - Gong, Wu; Aizawa, Kazuya; Harjo, Stefanus; Zheng, Ruixiao; Kawasaki, Takuro; Abe, Jun; Kamiyama, Takashi; Tsuji, Nobuhiro
Abstract: Hot extrusion is an effective process for strengthening magnesium alloys. In this study, we investigated the hot extrusion strengthening mechanism in an Mg97 Zn1 Y2 alloy with a duplex microstructure consisting of a long period stacking ordered (LPSO) phase and an α-Mg phase. The deformation behavior of Mg97 Zn1 Y2 alloys in the as-cast and as-extruded states was examined by in situ neutron diffraction during uniaxial compression tests. The results show that the yield strength of Mg97 Zn1 Y2 alloy was substantially enhanced by hot extrusion. The LPSO phase yielded at a rather low stress of −50 MPa in the as-cast alloy via basal slip. However, the LPSO phase persisted elastic behavior and shared additional lattice stress after the yielding of the α-Mg matrix until the onset of kink deformation at −289 MPa in the as-extruded alloy. The conjunction of basal slip in LPSO phase and the surrounding coherent α-Mg matrix is believed to be the reason for the relative low yield stress of the LPSO phase in the as-cast alloy. The quantitative evaluation of phase stress partition confirmed that the LPSO phase was significantly enhanced by hot extrusion and kink deformation of the LPSO phase plays an important role in preserving ductility. Highlights: Kink deformation and basal slip in the LPSO phase were examined by in situ neutron diffraction for the first time. Hot extrusion strengthening of the LPSO phase is much higher than that of the α-Mg phase Kink deformation activated in LPSO phase at higher stress than those of basal slip and twinning in α-Mg phase.